Update on canine filaggrin: a review. (1st January 2020) - Combarros, Daniel; Cadiergues, Marie-Christine; Simon, Michel
Abstract: Human filaggrin (FLG) plays a key role in epidermal barrier function, and loss-of-function mutations of its gene are primarily responsible for the development of human atopic dermatitis (AD). FLG expression is also reduced in the epidermis of atopic patients, due to the transcriptional effect of Th2 type cytokines. Canine atopic dermatitis (CAD) is a prevalent skin disease that shares many clinical and pathogenic features with its human homologue. The aim of this review is discuss current knowledge on canine filaggrin (Flg) in both healthy and atopic dogs, as compared to the human protein. Although the molecular structures of the two proteins, as deduced from the sequences of their gene, are different, their sites of expression and their proteolytic processing in the normal epidermis are similar. Concerning the expression of Flg in CAD, conflicting results have been published at the mRNA level and little accurate information is available at the protein level. It derives from a large precursor, named profilaggrin (proFLG), formed by several FLG units and stored in keratohyalin granules of the stratum granulosum. Canine and human proFLG sequences display little amino acid similarity (33% as shown using the Basic Local Alignment Search Tool (BLAST)) except at the level of the S100 homologous part of the N-terminus (75%). Genetic studies in the dog are at an early stage and are limited by the variety of breeds and the small number of cases included. Many questions remain unanswered about the involvement of Flg in CAD pathogenesis.